2010
DOI: 10.1002/app.32410
|View full text |Cite
|
Sign up to set email alerts
|

Thermogelling of highly branched poly(N‐isopropylacrylamide)

Abstract: Highly branched poly(N-isopropylacrylamide) (PNIPAM) has been synthesized by a reversible addition-fragmentation chain transfer (RAFT) copolymerization of NIPAM and a vinyl contained trithiocarbonate RAFT agent.1 H-NMR measurements revealed that the degrees of branch (DB) are in the range of 0.032-0.105. Laser light scattering (LLS) measurements gave the hydrodynamic radii (R h ) of the polymers to be 3.6-5.7 nm with molecular weight in the range of 1.3 Â 10 4 g/mol-2.3 Â 10 À4 g/mol. Highly branched PNIPAM wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…And the supramolecular LCHBPs presented in Figure also showed tunable upper critical solution temperature (UCST) around room temperature and LCST at high temperature, due to the formation of gel‐like aggregates resulting from supramolecular inclusion complexation or poor solubility of polyethylene glycol in water, respectively . Such kinds of thermo‐responsive poly( N ‐isopropyl acrylamide) LCHBPs were also reported by other groups with multi‐thiols capping, which can be oxidized by air to form disulfide bonds, resulting in the formation of nanoparticle in aqueous solution . A thermogelling behavior was also found for the nanoparticle system when heating it up to 20 °C, and the formed hydrogel showed thermo‐induced collapse when increasing temperature up to 35 °C, which made it possible to be applied in biomaterials …”
Section: Properties Of Lchbpsmentioning
confidence: 68%
“…And the supramolecular LCHBPs presented in Figure also showed tunable upper critical solution temperature (UCST) around room temperature and LCST at high temperature, due to the formation of gel‐like aggregates resulting from supramolecular inclusion complexation or poor solubility of polyethylene glycol in water, respectively . Such kinds of thermo‐responsive poly( N ‐isopropyl acrylamide) LCHBPs were also reported by other groups with multi‐thiols capping, which can be oxidized by air to form disulfide bonds, resulting in the formation of nanoparticle in aqueous solution . A thermogelling behavior was also found for the nanoparticle system when heating it up to 20 °C, and the formed hydrogel showed thermo‐induced collapse when increasing temperature up to 35 °C, which made it possible to be applied in biomaterials …”
Section: Properties Of Lchbpsmentioning
confidence: 68%
“…Previous studies have shown that end groups have significant effects on the transition temperature of linear pNIPAAm 24, 39. In our system, the RAFT groups double as the chain ends in our branching scheme and can be easily cleaved via aminolysis 33, 40. The remaining thiols can then be modified through thiol‐Michael addition chemistry 41–43…”
Section: Resultsmentioning
confidence: 97%
“…T , D , and L represent terminal, dendritic, and linear groups, respectively. DB and ANB are commonly used to describe the branching properties of highly branched polymers 17, 19, 33–35. ANB was calculated to be the ANB per nonterminal, nonlinear unit and the results of both parameters are shown in Table 1 32…”
Section: Resultsmentioning
confidence: 99%
“…DB and ANB are commonly used to describe the branching properties of highly branched polymers. 17,19,[33][34][35] ANB was calculated to be the ANB per nonterminal, nonlinear unit and the results of both parameters are shown in Table 1. 32 The DB values decreased with increasing amounts of 3Me3PenOH; however, the branching density remained constant.…”
Section: Effects Of Using a Bulky Alcohol Cosolventmentioning
confidence: 99%